SNORE (Sleep Deprivation Among Night Shift Health Staff on Rotation Evaluation) Study Protocol - Gnana Chellaiyan D, Vinoth; AY, Nirupama; G, Ravivarman (National Journal of Community Medicine, 2022)
Background: SNORE (Sleep deprivation among Night shift health staff On Rotation Evaluation) study is conceptualized to study the effects of sleep deprivation on healthcare professionals working night shifts on rotation. Materials and Methods: A comparative cross‑sectional study is devised including health‑care professionals working night shifts on rotation at a tertiary level health‑care facility, using a semi‑structured questionnaire which can test sleep deprivation, cognitive ability, and quality of life. The process is to approach 309 probable study participants based on stratified random sampling, after exclusion of health‑care professionals with other factors which may interfere with sleep deprivation testing. Discussion: The study protocol was set in such a way as to randomly include participants from all cadres of healthcare providers as per population proportion. By measuring the effects on cognitive effect and quality of life necessary steps can be taken to provide better quality of life and to decrease cognitive impairment, especially among health care professionals working night shifts.